2020
DOI: 10.3390/cancers12061434
|View full text |Cite
|
Sign up to set email alerts
|

Combined Targeting of Glioblastoma Stem-Like Cells by Neutralizing RNA-Bio-Drugs for STAT3

Abstract: An important drawback in the management of glioblastoma (GBM) patients is the frequent relapse upon surgery and therapy. A likely explanation is that conventional therapies poorly affect a small population of stem-like cancer cells (glioblastoma stem cells, GSCs) that remain capable of repopulating the tumour mass. Indeed, the development of therapeutic strategies able to hit GSCs while reducing the tumour burden has become an important challenge to increase a patient’s survival. The signal transducer and acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…GL21.T, an inhibitor ligand specific for receptor tyrosine kinase (RTK) Axl, is often used to target miR-10b, and we found that combined treatment with Gint4.T-STAT3 and GL21.T-anti-miR-10b complexes significantly abrogated the proliferation of GSCs. Here we found that the combined treatment of Gint4.T-STAT3 with GL21.T-10b resulted in a synergistic and drastic inhibition of GSC self-renewal (Esposito et al, 2020).…”
Section: Sirnas Targeting Stat3mentioning
confidence: 65%
“…GL21.T, an inhibitor ligand specific for receptor tyrosine kinase (RTK) Axl, is often used to target miR-10b, and we found that combined treatment with Gint4.T-STAT3 and GL21.T-anti-miR-10b complexes significantly abrogated the proliferation of GSCs. Here we found that the combined treatment of Gint4.T-STAT3 with GL21.T-10b resulted in a synergistic and drastic inhibition of GSC self-renewal (Esposito et al, 2020).…”
Section: Sirnas Targeting Stat3mentioning
confidence: 65%
“…Inhibition of STAT3, which functions both as a signal transducer and transcription factor, may also improve outcomes in GBM. Small interfering RNAs targeting STAT3 can reduce the GSC population in vitro and tumor growth in vivo [ 247 ]. Small molecule inhibitors of the STAT3 pathway include Stattic, which targets the SH2 domain of STAT3, and WP1066, which suppresses STAT3 activity and prevents its phosphorylation [ 123 , 248 ].…”
Section: Targeted Therapymentioning
confidence: 99%
“…The treatment of patient-derived GSC lines with the Gint4.T-STAT3 AsiC in combination with a chimera containing the anti-Axl aptamer GL21.T conjugated to an antagonist for microRNA (miR)-10b (GL21.T-10b) efficiently inhibited tumor sphere formation of GSCs, cell propagation, and invasion. 92,93 Recently, using differential cell-SELEX, Affinito et al 94,95 described a 2 0 F Py-modified RNA aptamer that selectively binds patientderived GSCs but not the same cells grown as adherent cells. The aptamer, named A40s, targets EphA2 on the cell surface of GSCs, inhibiting tumor growth stemness and migration.…”
Section: Targeting Cscsmentioning
confidence: 99%